DEVELOPMENT OF INTEGRATIVE CHARACTERISTICS TEACHER IN THE CONDITIONS OF PROFILE TRAINING FOREIGN LANGUAGE FOR FUTURE ENGINEERS - O.H. Kaverina (Academy of Cognitive and Natural Sciences, 2022)
The teacher integrative characteristics as the English Language education process managers are thought to be the whole unity of their professional activity psychological, pedagogical and subject components, necessary for the integration process implementation on the level of English Language various subject links.